Evaluating the consistency with guideline recommendations for diagnosis and management of idiopathic pulmonary fibrosis in non-academic settings - de Andrade, Joao; Luckhardt, Tracy; Sonavane, Sushilkumar; Crowe, D. Ralph; Kulkarni, Tejaswini; Acosta Lara, Maria del Pilar; gulati, Swati; Il-Kim, Young; Ramachandran, Rekha; O'Beirne, Ronan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background: Idiopathic pulmonary fibrosis (IPF) is a progressive lung disease with elevated mortality. Delay in diagnosis lead to worse outcomes. Guidelines developed at academic medical centers are difficult to replicate in the community.Objectives: Our primary objective was to ascertain consistency with the 2011 IPF guidelines. Our secondary objective was to conduct an interdisciplinary review to ascertain whether the evidence supported the original diagnosis of IPF or not.Methods: We asked permission from pulmonologists to review records of patients diagnosed with IPF after 2011. We collected physician demographics and training data; patient demographics, clinical and diagnostic/management data. The clinical data and available images were reviewed by the interdisciplinary review panel.Results: 26 practicing pulmonologists located in the Southeast of the United States consented to participate. Mean age was 48, 70% were male and all had current certification. We reviewed data from 96 patients. The mean age was 71.4 and most were male. Only 23% had the recommended screening for a connective tissue disease and 42.6% were screened for exercise-induced hypoxemia. Among patients with available images for review (n=66), only 50% had a high-resolution CT scan. 22% of patients underwent a surgical biopsy and in only 33% of the cases three lobes were sampled. No patient had documentation that a multidisciplinary discussion occurred. In 20% of the cases with available images, the evidence supported an alternative diagnosis. 56% of eligible candidates were ever started on anti-fibrotics.Conclusions: Our findings suggest that consistency with the IPF guidelines is low in non-academic settings.